LITERATURE REVIEW: TEORI MODEL WHOLE SCHOOL, WHOLE COMMUNITY, WHOLE CHILD DALAM KONTEKS KEPERAWATAN KOMUNITAS LINGKUP SEKOLAH - Rizkia Sukma Nurhaliza; Dinda Puput Purwanti; Sella Putri Herawadi; Muhammad Ghifari Firdaus; Sabrina Stacia Aurelia; Tirta Adikusuma Suparto (STIKES Pemkab Purworejo, 2024)
Background: Collaboration and advocacy between school nurses, educators, parents and healthcare providers can create a supportive and healthy school environment for students. Effective collaboration and communication between school nurses, teachers, parents, and healthcare providers is necessary to ensure coordinated care for students. Whole School, Whole Community, Whole Child (WSCC) is an effort to meet the educational and health needs of young people that encompasses the entire school. The model outlines a whole-school approach, with every adult; teacher and nurse, and every student playing a role in the growth and development of themselves, their peers, and the school as a whole. Objective: to describe the results of a literature review on the theoretical description of the WSCC model in the context of school health nursing. Method: using the literature review method of 10 journal articles published in the range of 2020-2023 with reference sources from the Google Scholar database and PubMed. Results: of the 10 articles that were successfully obtained explained the description of the WSCC model, implementation, policy, and urgency. Conclusion: WSCC is an effective framework in improving student well-being in schools equipped with several implementation tools.